Sphingosine 1-phosphate receptor 2 in keratinocytes plays a key role in reducing inflammation in psoriasis - Masuda-Kuroki, Kana; Alimohammadi, Shahrzad; Lowry, Samantha; Di Nardo, Anna (Frontiers in Immunology, 2024)
Background: Psoriasis is an inflammatory skin condition where immune cells play a significant role. The importance of the cross-talk between keratinocytes and immune cells in the pathogenesis of psoriasis has recently been reaffirmed. Recent studies have found that several S1PR functional antagonists, other than S1PR2, are effective in improving psoriasis. This study aims to investigate the role of S1PR2 in psoriasis, that has not been investigated before. Methods: Spatial transcriptomics, RT-qPCR, and flow cytometry were used to map the immune cell landscape and its association with metabolic pathways in an imiquimod (IMQ)-induced psoriasis-like inflammation in S1pr2fl/fl K14-Cre mice that could not sense sphingosine-1-phosphate (S1P) in the epidermis through the S1PR2 receptor. Results: Our analysis suggests that S1PR2 in keratinocytes plays a major role in psoriasis-like inflammation compared to other S1PRs. It acts as a down-regulator, inhibiting the recruitment of Th17 cells into the skin. In IMQ-induced psoriasis skin, both S1pr2-/- and S1pr2fl/fl K14-Cre mice showed higher expressions of proinflammatory cytokines such as TNF-α, IL-17A, and IL-1β together with higher expressions of MyD88/NF-κB pathway compared to the wild-type mice. Remarkably, in IMQ-treated mice, the deletion of S1pr2 in keratinocytes only resulted in a larger population of Th17 cells in skin-draining lymph nodes. Other S1PR modulators did not improve the worsening of psoriasis-like inflammation caused by S1PR2 deficiency in keratinocytes. Conclusions: This study reaches two main conclusions: signals from keratinocytes play a central role in creating an immune environment that promotes the development of psoriasis, and stimulating S1PR2, instead of suppressing it, represents a potential therapeutic approach for psoriasis.